The Quality of Neighbourhood Facilities and Their Effect on Social Trust in Salak Selatan New Village, Kuala Lumpur - Norhaslina Hassan; Tricia Su Ying Lim (The Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
This study investigated neighbourhood amenities as socio-spatial settings within which relationships of trust are built through the passage of daily activities. It examined the effect of satisfaction towards neighbourhood facilities on social trust in one of Malaysia's urban villages: Salak South New Village in Kuala Lumpur. Data from 335 survey respondents were analysed using the MANOVA method to determine the influence of neighbourhood facilities satisfaction on social trust. To achieve the aim of this study, five independent variables (IVs) of satisfaction with provided selected neighbourhood facilities were considered: basic utilities, commercial facilities, health facilities, police service and public transport, while two dependent variables (DV) of communal trust and leadership trust were identified that constitute social trust. The findings reveal that satisfaction towards neighbourhood facilities significantly influenced social trust among the respondents. Multivariate analysis showed commercial facilities as the most influential in determining social trust, followed by public transport, health facilities, basic utilities, and finally police service. Therefore, improving neighbourhood facilities and amenities will enhance the satisfaction of residents and accordingly increase social trust. In other words, unmaintained and underdeveloped facilities lessen social trust in a community via resident dissatisfaction. This necessitates engagement of stakeholders including urban planners, local authorities and the residents themselves in the planning process and village development to ensure that the residents will be satisfied with changes for better neighbourhood facilities and social trust is sustained.Abstrak. Makalah ini mempelajari keberadaan fasilitas lingkungan dalam konteks sosio-spasial yang menjadi tempat terbangunnya hubungan kepercayaan melalui perjalanan aktivitas sehari-hari. Makalah ini menguji pengaruh kepuasan terhadap fasilitas lingkungan pada kepercayaan sosial di salah satu desa perkotaan Malaysia - Desa Baru Selatan Salak, di Kuala Lumpur. Data dari 335 responden dianalisis menggunakan metode MANOVA untuk menjelaskan pengaruh kepuasan fasilitas lingkungan terhadap kepercayaan sosial. Untuk mencapai tujuan penelitian ini, ditentukan lima variabel independen (IV) yang dapat mewakili kepuasan terhadap penyediaan fasilitas lingkungan yang dipilih: utilitas dasar, fasilitas komersial, fasilitas kesehatan, layanan polisi dan angkutan umum; sedangkan dua variabel dependen (DV):Kepercayaan komunal dan kepercayaan kepemimpinan diidetifikasi sebagai yang merupakankepercayaan sosial Hasil penelitian mengungkapkan bahwa kepuasan terhadap fasilitas lingkungan berpengaruh secara signifikan terhadap kepercayaan sosial di kalangan responden. Analisis multivariat menunjukkan fasilitas komersial sebagai yang paling berpengaruh dalam menentukan kepercayaan sosial; diikuti oleh angkutan umum, fasilitas kesehatan, utilitas dasar, dan terakhir layanan polisi. Oleh karena itu, peningkatan fasilitas dan amenitas lingkungan akan meningkatkan kepuasan penghuni dan karenanya meningkatkan kepercayaan sosial. Dengan kata lain, fasilitas yang tidak terawat dan terbelakang mengurangi kepercayaan sosial dalam masyarakat melalui ketidakpuasan warga. Hal ini membutuhkan keterlibatan pemangku kepentingan termasuk perencana kota, pemerintah daerah dan warga sendiri dalam proses perencanaan dan pembangunan desa untuk memastikan bahwa penduduk desa puas dengan perubahan untuk fasilitas lingkungan yang lebih baik dan kepercayaan sosial dipertahankan.Kata kunci. Kepercayaan sosial, Kepuasan fasilitas, Kelurahan, Ruang lingkungan, Kuala Lumpur.